If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3a + -5b + 5c) = 0 (3a * -1 + -5b * -1 + 5c * -1) = 0 (-3a + 5b + -5c) = 0 Solving -3a + 5b + -5c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5b' to each side of the equation. -3a + 5b + -5b + -5c = 0 + -5b Combine like terms: 5b + -5b = 0 -3a + 0 + -5c = 0 + -5b -3a + -5c = 0 + -5b Remove the zero: -3a + -5c = -5b Add '5c' to each side of the equation. -3a + -5c + 5c = -5b + 5c Combine like terms: -5c + 5c = 0 -3a + 0 = -5b + 5c -3a = -5b + 5c Divide each side by '-3'. a = 1.666666667b + -1.666666667c Simplifying a = 1.666666667b + -1.666666667c
| 65+x(x-5)=180 | | -7x-15+9x+23=2 | | r/2=11/8 | | 10b-2=4b-14 | | -(5x-10)=5 | | -5+2x-7x=35 | | a=160m+215 | | 4x-22=2x+12 | | -4m+2+1m=23 | | 2p-3=7 | | 15m+4-9m= | | -3x-7x=97 | | 6x+6=-x+55 | | 0.5=0.4y-0.25y | | 2x+6=4x+12 | | 3(-3x-2)-4x-5=-3 | | 5x-2x=168 | | .4(x-12)=1.2(x-4) | | 2(3a-4.2)=5a | | 6g-9/3=g | | 4(m+1)-2(3m+1)=-3(m-7)+5 | | z-2/3=1/8 | | 3(s+1)-5=3s-2 | | 5x-27=-4x | | -4-5x=7-x | | 5x+9+8=4 | | 2.85s-7=12.85s-2 | | ax+by=c(y) | | 2(x+5)+3= | | 2.5(x-2)-6=9 | | -2x-9=3x+4 | | b-31=-63 |